Portraiture in South Asia since the Mughals : art, representation and history - Branfoot, Crispin (London ; New York : I.B. Tauris & Co. Ltd., 2018)
Deriving from Persian artistic techniques, Mughal portraiture reached its apogee during the reigns of the great Mughal emperor-patrons Akbar, Shah Jahan and Jahangir. Much of the art produced in this period was commissioned for political reasons, and art was one method of ensuring power, increasing prestige and sending messages to the kingdom and rival dynasties. Western portraiture has become an incredibly important source of historical study because of what it can tell us about the tastes, rules, dress, politics and identity of periods and rulers. One of the reasons this hasn't quite happened for Mughal painting is that we often think of these paintings as authorless, but of course the great Mughal artists were in demand, and were able to bring unique skills to their work--the Emperor Jahangir claimed to be able to instantly recognize an artist's work by sight. This collection seeks to enrich our understanding of Mughal culture through its portraiture, examining the artistic conventions and cultural norms from the Persianate early works through to the Europeanization of South Asian traditions in the 19th century and the continuation of the tradition today. A specially commissioned collection of studies from an exceptionally strong list of established scholars and rising stars on both sides of the Atlantic; this marks a major breakthrough in South Asian history.
9. The Role of Portraiture in Pakistani Contemporary Miniature Painting: The 'Mughal Connection'Chance; Artists; Bibliography; Index
Includes bibliographical references (pages 249-265) and index
Print version record.
eBooks on EBSCOhost
Keywords: Painting, Mughal Empire -- History; Painting, Mughal Empire -- Influence; Islamic art -- South Asia; Peinture moghole -- Histoire; Peinture moghole -- Influence; Art islamique -- Asie méridionale.; ART -- History -- General; Islamic art; Painting, Mogul Empire; South Asia; History